Immunomodulatory Effect of Ginsenoside Rb2 Against Cyclophosphamide-Induced Immunosuppression in Mice - Zheng, Siwen; Zheng, Housheng; Zhang, Rui; Piao, Xiangmin; Hu, Junnan; Zhu, Yanzhu; Wang, Yingping (Frontiers in Pharmacology, 2022)
Ginsenoside Rb2 (Rb2), a fundamental saponin produced and isolated from ginseng (Panax ginseng C.A. Meyer), has a wide range of biological actions. The objective of this investigation was to see if ginsenoside Rb2 has any immunomodulatory properties against cyclophosphamide (CTX)-induced immunosuppression. For the positive control group, levamisole hydrochloride (LD) was used. We discovered that intraperitoneal injection of Rb2 (5, 10, 20 mg/kg) could relieve CTX-induced immunosuppression by enhanced immune organ index, reduced the pathological characteristics of immunosuppression, promoted natural killer (NK) cells viability, improved cell-mediated immune response, boosted the IFN-γ (Interferon-gamma), TNF-α (Tumor necrosis factor-alpha), IL-2 (Interleukin-2), and IgG (Immunoglobulin G), as well as macrophage activity like carbon clearance and phagocytic index. Rb2 significantly elevated the mRNA expression of IL-4 (Interleukin-4), SYK (Tyrosine-protein kinase-SYK), IL-2, TNF-α, and IL-6 (Interleukin-6) in the spleen of CTX-injected animals. Molecular docking results showed that Rb2 had excellent binding properties with IL-4, SYK, IL-2, TNF and IL-6, indicating the target protein might be strongly correlated with the immunomodulatory effect of Rb2. Taken together, ginsenoside Rb2 can improve the immune function that is declined in CTX-induced immunosuppressed mice, the efficacy maybe due to the regulation of related cytokine and mRNA expression.